HIV virological rebounds but not blips predict liver fibrosis progression in antiretroviral‐treated HIV/hepatitis C virus‐coinfected patients. Issue 1 (18th May 2014) - Cooper, C; Rollet‐Kurhajec, KC; Young, J; Vasquez, C; Tyndall, M; Gill, J; Pick, N; Walmsley, S; Klein, MB; the Canadian Co‐infection Cohort Study Investigators
<x xml:space="preserve">Abstract</x> Objectives Antiretroviral interruption is associated with liver fibrosis progression in HIV/hepatitis C virus (HCV) coinfection. It is not known what level of HIV viraemia affects fibrosis progression. Methods We evaluated 288 HIV/HCV‐coinfected cohort participants with undetectable HIV RNA (< 50 HIV‐1 RNA copies/mL) on two consecutive visits while on combination antiretroviral therapy (cART) without fibrosis [aspartate aminotransferase to platelet ratio index (APRI) < 1.5], end‐stage liver disease or HCV therapy. An HIV blip was defined as a viral load of ≥ 50 and < 1000 copies/mL, preceded and followed by undetectable values. HIV rebound was defined as: (i) HIV RNA ≥ 50 copies/mL on two consecutive visits, or (ii) a single HIV RNA measurement ≥ 1000 copies/mL. Multivariate discrete‐time proportional hazards models were used to assess the effect of different viraemia levels on liver fibrosis progression (APRI ≥ 1.5). Results The mean age of the patients was 45 years, 74% were male, 81% reported a history of injecting drug use, 51% currently used alcohol and the median baseline CD4 count was 440 [interquartile range (IQR) 298, 609] cells/μL. Fifty‐seven (20%) participants [12.4/100 person‐years (PY); 95% confidence interval (CI) 9.2−15.7/100 PY] progressed to an APRI ≥ 1.5 over a mean 1.1 (IQR 0.6, 2.0) years of follow‐up time at risk. Virological rebound [hazard ratio (HR) 2.3; 95% CI 1.1, 4.7] but not blips (HR 0.5; 95% CI 0.2, 1.1) predicted progression to APRI ≥ 1.5. Each additional 1 log10 copies/mL HIV RNA exposure (cumulative) was associated with a 20% increase in the risk of fibrosis progression (HR 1.2; 95% CI 1.0–1.3). Conclusions Liver fibrosis progression was associated with HIV rebound, but not blips, and with increasing cumulative exposure to HIV RNA, highlighting the importance of achieving and maintaining HIV suppression in the setting of HIV/HCV coinfection.